Analysis of the Correlation Between Rainfall Intensity and Water Level at Machap Dam Catchment Area - Nur Tijani Ilmi Zulkiflie,; Arrthy Nair Paramasivam,; Puteri Alya Adriana Yusuan,; Suhaila Sahat, (Multidisciplinary Applied Research and Innovation, 2024)
Measuring and recording weather elements such as rainfall, temperature, and moisture is critically important in industries, agriculture, aviation, hydrology, and engineering. This research is conducted to evaluate the use of the Normal Ratio Method to estimate rainfall missing data and whether there will be a significant result between rainfall data from 5 total stations and the water level at the Machap Dam catchment area. The correlation between rainfall intensities and water level at Machap Dam was determined by first obtaining missing data at the 5 total stations using the Normal Ratio Method. The study area involved Kluang, Johor. Based on the analysis of rainfall missing data it shows that a minimum of 5 total stations are sufficient to obtain the data. Meanwhile, the correlation between rainfall and dam water level indicates only 1 station has a correlation with R square 0.67, and the other 4 stations have recorded less than 0.5 of the R square values. From the analysis, it can be concluded that the study for short-term periods of rainfall data is irrelevant due to the insufficiency of data collection.